School egress data: comparing the configuration and validation of five egress modelling tools. (10th October 2016) - Cuesta, Arturo; Ronchi, Enrico; Gwynne, Steven M. V.; Kinsey, Michael J.; Hunt, Aoife L. E.; Alvear, Daniel
Summary: Data were collected between 2011 and 2014 from five evacuations involving the same school buildings located in Spain. Children from 6 to 16 years of age were observed during the evacuation exercises. Background information was collected on key factors deemed to influence evacuation performance: a description of the geometry, the population involved, the procedures employed and the organization of the drills conducted. Using live observations and video footage of these drills, evacuation data were collected, focusing on the pre‐evacuation times, the routes employed, the travel speeds adopted and the arrival times. These data informed a range of a posteriori simulations, conducted by using four computer models (buildingEXODUS, MassMotion, Pathfinder and STEPS) and the Society of Fire Protection Engineering hydraulic model (i.e. Society of Fire Protection Engineering hand calculations). Comparisons were drawn between the models' output and against the observed outcome for one of the trials to determine the accuracy of the model predictions given that they were configured by using the initial conditions for a specific evacuation. The purpose of this work is to (1) provide insight into the configuration of these models for equivalent scenarios, (2) examine any variation in the simulated conditions given equivalent initial conditions, and (3) provide suggestions on how to perform validation studies for multiple evacuation models. Copyright © 2016 John Wiley & Sons, Ltd.